KONSTRUKSI HUKUM PERCERAIAN ISLAM DALAM FIQH INDONESIA - Mohsi Mohsi (Ulumuna: Jurnal Studi Keilsman, 2015)
The construction of divorce law in Indonesia give many contributions to the fiqh law development, as a development of Islamic law philosophy. So the reformulation with various shapes without changing the provision and principle of fiqh law, is an intellectual richness that must be strained as a responsibility to the complexity of people’s issues. Therefore, the substance and purposes of syariah in the Qur’an and formulated by ‘ulama ushul fiqh can not be seen in the fiqh book for centuries, but also Indonesian Islamic law product reflects Maqôsid al-Syarîah becoming law purpose